Liminal Spaces: When the European “Intellectual” Meets the American “Savage” - Magnarelli, Sharon (Latin American Theatre Review, 2016)
Both Lucía Laragione and Pedro Sedlinsky in their respective Criaturas del aire and El informe del Dr. Krupp stage the encounter of the European “scientist/intellectual” with the American “primitive/savage.” Employing postcolonial theory, this articles analyzes how the European intellectual invades American space (implicitly “primitive” or “savage,” since it is defined as “not European”) while reconstructing the European space. In both cases, the Europeanized space is an interior space, while the American space is depicted as exterior in an underscoring of the perceived binary divisions between civilization and nature, mind and body, intellectual and primitive. Nonetheless, and in what the author reads as fundamental to the playwrights’ messages, although the “civilized” space of the European intellectual is the focus of the action in both plays, the “primitive,” American space is always visibly present and threatens to overflow its boundaries and spill into the “civilized,” European space.